Percutaneous extraction of a large device-related thrombus on a Watchman™ device: a case report. Issue 1 (16th December 2021) - Vyas, Rhea; Kohler, Cassidy; Pershad, Ashish
Abstract: Background: Left atrial appendage occlusion devices are commonly used to prevent stroke in patients with persistent atrial fibrillation who are unable to tolerate anticoagulation. However, certain patient- and device-related characteristics increase the risk for the development of a device-related thrombus (DRT). The presence of a DRT increases the risk of stroke and should be treated. Management of DRT lacks consensus but is mostly focused on anticoagulation. In patients with large thrombi that need to be managed urgently, percutaneous extraction may be a viable option. Case summary: In this report, we describe the successful management of a DRT via percutaneous thrombus extraction technology in an 81-year-old woman with a large thrombus attached to a WATCHMAN™ device. The patient initially presented with shortness of breath, and on imaging a pedunculated thrombus was detected. The thrombus was extracted using a Penumbra Lightning 12™ (Penumbra Inc., Alameda, CA, USA) catheter with a Sentinel™ (Boston Scientific, Marlborough, MA, USA) cerebral embolic protection device. The patient had no neurologic sequelae and was started on anticoagulation. Discussion: Percutaneous thrombectomy can be safely performed to extract large left atrial occlusion DRT that require urgent management, without any neurologic sequelae. We believe this can be used in patients with a large DRT who would not be adequately managed with anticoagulation and in whom surgery is not feasible.